INCREASING PEDAGOGIC COMPETENCY AND PROFESSIONAL COMPETENCY THROUGH EDUCATION AND TRAINING DEVELOPMENT OF SUSTAINABLEPROFESSION OF DEVELOPMENT (Case Study of Kindergarten Teachers in Bandung) - Rita Nurunnisa (IKIP Siliwangi Bandung, 2018)
ABSTRACTTeacher competence is the teacher's capital in carrying out the main task and its function in educating the students. There are 4 competencies that must be possessed by teachers, namely, pedagogic competence, professional competence, personality competence and social competence. Teachers should have awareness in themselves to continue to learn and develop themselves continuously in an effort to improve services to learners. One of the teacher's efforts in self-development is through education and training. For that, the authors examine the